2012
DOI: 10.1155/2012/293156
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Impedance Changes at the Fetal Brain Vessels in a Pregnancy Affected with a Multiple Combination of Uteroplacental Anomalies

Abstract: A fetus with a very rare five-fold combination of uteroplacental anomalies, bicornuate uterus, short cervix with cervical incompetence, multilobed placenta succenturiata, accessory cotyledon within the cervical funneling, and umbilical cord insertion into the anomalous cervical cotyledon, presented an early and marked decrease at the vertebral and middle cerebral arteries Doppler resistances. This cerebral low-impedance state, usually found before labor, and considered an adaptive mechanism developed to protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A total of 963 studies were screened. Of these, 48 studies comprising 1625 pregnant women with abnormal placenta and 167,566 pregnant women without abnormal placentas met the inclusion criteria of the current systematic review for descriptive analysis [ 3 , 9 , 10 , 11 , 12 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 963 studies were screened. Of these, 48 studies comprising 1625 pregnant women with abnormal placenta and 167,566 pregnant women without abnormal placentas met the inclusion criteria of the current systematic review for descriptive analysis [ 3 , 9 , 10 , 11 , 12 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…The metadata of the 48 eligible studies are shown in Supplementary Table S1 [ 3 , 9 , 10 , 11 , 12 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The eligible studies were published between 1974 and 2022.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations